Peranan Madu 15% Terhadap Peningkatan pH Saliva Wanita Menopause - Syahrul, Dwis; Dewi, Tri Purnami; Sulistyawati, I G A P Oka (Interdental: Jurnal Kedokteran Gigi, 2017)
Fructose, which is the highest concentration of substance in honey, can stimulate saliva more than sucrose, so it is considered to affect the acidity (pH) of saliva, especially postmenopausal women who generally experience a decrease in salivary pH. This study aims to determine the ratio of salivary pH of menopausal women who rinse with drinking water and rinse with 15% concentrated honey. A sample of 32 postmenopausal women between the ages of 50-60 years were divided into 2 groups, namely the control group and the treatment group. Before being treated, the initial salivary pH of the two groups was recorded. Then the control group was instructed to rinse with drinking water and the treatment group was instructed to rinse with 15% honey. Both groups rinsed at the same time for 3 minutes. Then the salivary pH of each group is measured. Data analyzed by independent t-test between the two groups, showed a significance value of 0.037 in the control group and 0.041 in the treatment group (p <0.05). Paired t-test conducted in each group produced a significance value of 0.164 for the control group and 0.07 for the treatment group (p <0.05). Gargling with honey 15% can significantly increase the salivary pH of menopausal women compared to gargling with drinking water.